2020
DOI: 10.1038/s41586-020-03056-z
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin 5 mediates virus-induced autophagy and immunity

Abstract: Autophagy, a lysosomal degradation pathway, plays an essential role in multiple aspects of immunity, including immune system development, regulation of innate and adaptive immune and inflammatory responses, selective degradation of intracellular microbes, and host protection against infectious diseases 1 , 2 . Unlike autophagy induction by stimuli such as nutrient deprivation and mTOR suppression, little is known about how autophagosomal biogenesis is initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 55 publications
0
81
0
Order By: Relevance
“…Autophagy is inhibited by the hyperactivation of AKT/mTOR signaling 15,16 . Therefore, we investigated the influence of H 2 O 2 on autophagy in LUAD cells and observed that H 2 O 2 at a proliferative concentration suppressed rapamycin (Rapa)‐induced autophagy, which could be counteracted by AQP3 depletion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is inhibited by the hyperactivation of AKT/mTOR signaling 15,16 . Therefore, we investigated the influence of H 2 O 2 on autophagy in LUAD cells and observed that H 2 O 2 at a proliferative concentration suppressed rapamycin (Rapa)‐induced autophagy, which could be counteracted by AQP3 depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is inhibited by the hyperactivation of AKT/mTOR signaling. 15 , 16 Therefore, we investigated the influence of H 2 O 2 on autophagy in LUAD cells and observed that H 2 O 2 at a proliferative concentration suppressed rapamycin (Rapa)‐induced autophagy, which could be counteracted by AQP3 depletion. In a tissue Microarray (TMA) containing tissues from 74 LUAD patients, we tested the relationships between AQP3, 8‐hydroxy‐2′‐deoxyguanosine (8‐oxo, an oxidative stress biomarker) and p62 (SQSTM1, an autophagosome marker).…”
Section: Introductionmentioning
confidence: 99%
“…The macropinocytosis is adapted as an alternative means of nutrient source to allow sustained fetal growth, which is greatly enhanced during amino acid shortage 18, 19 . In addition, it has been reported that SNX5 stimulated autophagy during viral infection 20 . In cattle, amino acids are essential for the survival and development of embryo 14,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent genome-wide short interfering RNA screen study showed that virion-containing endosomes can be targeted for virophagy. The endosomal protein sorting nexin 5 (SNX5) interacts with ATG14-containing class III phosphatidylinositol-3-kinase complex 1 (PI3KC3-C1) upon HSV-1 (ICP34.5 Δ68–87 ) infection and increases the lipid kinase activity of PI3KC3-C1, which in turn promotes endosomal generation of phosphatidylinositol-3-phosphate (PtdIns(3)P), and recruitment of (PtdIns(3)P)-binding protein WIPI2 to virion-containing endosomes [ 111 ].…”
Section: Viral Xenophagy (Virophagy)mentioning
confidence: 99%